Infection by Diverse HIV-1 Subtypes Leads to Different Elevations in HERV-K Transcriptional Levels in Human T Cell Lines - Li, Xi; Guo, Yaolin; Li, Hanping; Huang, Xiaofeng; Pei, Zhichao; Wang, Xiaolin; Liu, Yongjian; Jia, Lei; Li, Tianyi; Bao, Zuoyi; Wang, Xiaorui; Han, Leilei; et al. (Frontiers in Microbiology, 2021)
Human endogenous retroviruses(HERVs) make up about 8% of the human genome, and for millions of years they have been subject to strict biological regulation. Many of them do not participate in normal physiological activities in the body. But in some pathological conditions, it can be abnormally activated. HIV infection can make the human endogenous retroviruses(HERVs) abnormal activation, under the condition of different infections its expression is also different. We found significant differences in HERV-K transcription levels among HIV-1 subtype infected individuals. The transcriptional levels in the HERV-K gag region were significantly increased in HIV B subtype infected patients, while the transcriptional levels in the HERV-K pol region were significantly increased in CRF01_AE and CRF07_BC subtype infected patients. In vitro, the transcriptional levels of HEVR-K were increased 5-fold and 15-fold in the two different HIV-1 strains (B, CRF01_AE) transfected MT2 cells, respectively. However, there was no significant difference in transcriptional levels among regions of HERV-K. When MT2 cells were infected with different subtypes Tat proteins of HIV-1(B, CRF01_AE), the transcription levels of HERV-K were increased 4-fold and 2-fold, respectively. Thus, different subtypes of HIV-1 have different effects on HERV-K transcription level, which may be caused by many factors, not only Tat protein.